PENGARUH SUSTAINABILITY REPORTING TERHADAP KINERJA KEUANGAN DARI SISI MARKET VALUE RATIOS - marni, Jus (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
Sustainability report contains the financial performance and non financial performance. Inrecent years, has been realized the importance of this disclosure through its impact on financialperformance.This study aimed to examine the relationship between indicators of sustainabilityreporting and the company’s market value ratios. This study used secondary data. The independenvariable in this study was disclosure of Sustainability report that divided into the performances ofdisclosure of economic, environmental, and social that measured by using SRDI Indexs. TheIndependent variables were measured by using the disclosure indexs. GRI (Global ReportingInitiative) would be used as a guade of sustainability report as a basis for measuring the indexs.The dependent variable used ware the market value ratios. the sample was 15 companies thatpublised the sustainability report in three consecutive years of 2010-2012 and could be accessedthrough the companies’ websites and website of National Center for Sustainability Reporting andthese companies had already published the Annual Financial Statements in 2011-2013 which couldbe accessed through the companies’ websites. As a result sustainability reporting in the economicand environmental aspect gave significant positive affect of Ratio Market Value, mean while in thesocial aspect, Sustainability Reporting gave not significant positive effect of Ratio market value.Keywords: Sustainability reporting, financial performance, market value ratios, Global ReportingIntiative-Index (GRI-Index)